DEVELOPING A TAQWA-BASED INVESTMENT CONCEPT - Muhammad Ridwan Fachri; Dahlifah (Universitas Islam Negeri Alauddin Makassar, 2024)
This research intends to develop a Taqwa-oriented investing framework. This research employs a qualitative methodology grounded in an Islamic paradigm characterized by Taqwa. The application of Taqwa traits to investment include Faith-based Investment, Promise-based Investment, and Patience Investment. This study was carried out at PT LBS Urun Dana, a firm involved in Securities Crowdfunding.This study's results indicate that LBS Urun Dana incorporates the Taqwa character in its investment practices. Faith-based investment implementation involves conducting prayers in the mosque and offering Islamic studies on muamalah maaliyah for both internal and external stakeholders, including businessman, investors, and the general public. LBS Urun Dana is a promise-based investment that adheres to commercial commitments in accordance with the directives of Allah and His Messenger. Patience-based investment employs patience to guide entrepreneurs and investors at LBS Urun Dana, enabling them to conduct business in accordance with Sharia principles. Taqwa-based investing is conducted exclusively to attain Allah's pleasure for fulfillment in both this life and the afterlife.